Effects of Ramadan fasting on anthropometric and body composition changes according to ADRB2 rs1042714 genotype - Aurellia Juneata Marsha; Rachmania Anggita Savitri; Monica Hermina Sharon Otline Yocku; Arynal Haq; Nani Maharani; Achmad Zulfa Juniarto; Ninik Rustanti; Adriyan Pramono (Jurnal Gizi Klinik Indonesia, 2026)
Background: Obesity is a metabolic disorder characterized by excessive fat accumulation. Intermittent fasting, including Ramadhan fasting, has been shown to regulate eating patterns and reduce the risk of obesity. Genetic variations in the ADRB2 gene, particularly rs1042714, may influence differences in anthropometric and body composition responses to Ramadan fasting between genotype groups via β2-adrenergic signalling.Objective: This study aimed to analyze the effects of Ramadan fasting on anthropometric and body composition changes between ADRB2 rs1042714 genotype groups.Methods: The natural experiment within a cohort design included 35 adults (8 males and 27 females) aged 19–52 years from Semarang, Indonesia. Repeated measurements were obtained over approximately seven weeks: one week before Ramadan, during the third week of Ramadan, and two weeks after Eid al-Fitr. The ADRB2 rs1042714 genotype data were obtained from a previous study and had been determined using a TaqMan allelic discrimination assay using real-time polymerase chain reaction (PCR). Waist circumference was measured with a Medline tape, body weight and body composition with an Omron HBF-214 bioelectrical impedance analyzer, and height with a stadiometer. Dietary intake was assessed using a semi-quantitative food frequency questionnaire (SQ-FFQ), whereas physical activity was assessed using the International Physical Activity Questionnaire-Short Form (IPAQ-SF). Differences between genotype groups were analyzed using t-tests or Mann–Whitney tests, as appropriate.Results: The CG+GG group (n = 10) exhibited significantly greater reductions in body weight (p = 0.016), BMI (p = 0.046), and visceral fat (p = 0.028) than the CC group (n = 25) during Ramadan fasting. Changes in physical activity also differed significantly between genotype groups during Ramadan fasting (p = 0.041). Conclusion: ADRB2 rs1042714 may contribute to interindividual variability in anthropometric and body composition changes during Ramadan fasting, with G-allele carriers exhibiting greater reductions in body weight, BMI, and visceral fat.